2015
DOI: 10.1111/asj.12482
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and composition responds to dietary neutral detergent fiber and starch ratio in dairy cows

Abstract: This study was designed to investigate whether dietary neutral detergent fiber (NDF) : starch ratio could be considered as a nutritional indicator to evaluate carbohydrate composition and manipulate milk production and composition synthesis. Eight primiparous dairy cows were assigned to four total mixed rations with NDF : starch ratios of 0.86, 1.18, 1.63 and 2.34 from T1 to T4 in a replicated 4 × 4 Latin square design. Dry matter intake and milk production were decreased from T1 to T4. Digestibility of dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Thus, the increase of milk fat content with increasing NDF:starch ratio could partially be described by enhanced NDF contents at the expense of starch. This is in agreement with Zhao et al [ 29 ] that milk fat concentration was increased linearly when increasing NDF:starch ratio of diets from 0.86 to 2.34 due to the surge of the molar proportion of acetate in the rumen. In another study, Jenkins and McGuire [ 33 ] also reported that the acetate and butyrate which are contributing from NDF serve as the major precursors to support milk fat synthesis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, the increase of milk fat content with increasing NDF:starch ratio could partially be described by enhanced NDF contents at the expense of starch. This is in agreement with Zhao et al [ 29 ] that milk fat concentration was increased linearly when increasing NDF:starch ratio of diets from 0.86 to 2.34 due to the surge of the molar proportion of acetate in the rumen. In another study, Jenkins and McGuire [ 33 ] also reported that the acetate and butyrate which are contributing from NDF serve as the major precursors to support milk fat synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…However, DMI as a percentage BW decreased with increasing starch content of diets. In another study, similar DMI was reported within NDF:starch range of 0.86–1.18, and intake was reduced with the further increase of NDF:starch ratio up to 2.34 [ 29 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Ammonia was measured using an adapted version of the phenol/hypochlorite method (Broderick and Kang, 1980). Feces samples (100 g) were collected every 6 h in the last 3 d of the experiment, and then each set of samples was mixed (Zhao et al, 2016). The pooled fecal sample was divided into 2 portions; then, 10% (vol/vol) 6 M HCl was added to one subsample for subsequent nitrogen analysis to one subsample, and the other was stored at −20°C for subsequent analysis of Se concentration, DM, OM, NDF, ADF, and ether extract (EE).…”
Section: Short Communicationmentioning
confidence: 99%